The Role of SATLINMAS in Actualizing Public Safety and Order (Faculty of Social Science, Universitas Negeri Semarang, 2021)
One of the manifestations of Sishankamrata (people's defense and security system) in the society is the formation of the Community Protection Unit (Satlinmas) as a public component that collaborates with TNI and POLRI in realizing security and public order (Kamtibmas). As the capital of Central Java Province, Semarang City, of course, has to maintain environmental peace and security. Therefore, the participation Satlinmas is essential in maintaining security and public order in Semarang City. To realize the good performance of Satlinmas in carrying out their duties and functions, capacity building efforts are needed among its members. Therefore, the Semarang City Government, in this case, the Civil Service Police Unit of Semarang, needs to prepare an identification of the Regional Linmas Unit following the direction of city development. This research was a mixed type of study (qualitative and quantitative) that was conducted to identify the condition of the Regional Linmas Unit in Semarang City. The subjects of this study consisted of members of the Linmas Unit in Semarang City. Sources of data in this study consisted of primary and secondary data sources that were collected using questionnaires, interviews, and documentation. Data analysis was performed using quantitative descriptive and interactive analysis methods. The results point out that the condition of Linmas of Semarang City still has many shortcomings in individual, institutional, and systemic aspects. The individual capacity of its members is not very good. This condition requires capacity building efforts that must be realized, especially at the individual level. This individual capacity development seeks to improve the quality of human resources through the development of personal skills, knowledge, and abilities needed in the organization. Besides, community participation is also very necessary to support Sishankamrata.